Implikasi Hukum Surah Al-Fatihah dalam Jami' Al-Bayan'an Ta'Wil Ayy Al-Qur'an Karya Ibn Jarir Al-Thabariy - Kasjim Salenda (AL-Fikr, 2013)
Among the narrative based exegesis books is Jami 'al-Ayy Bayan'an ta'wil al-Qur'an, better known as the exegesis of Ibn Jarir al-Thabariy, which identified with his name: Abu Ja'far Muhammad ibn Jarir ibn Yazid ibn Kathir ibn Ghalib al-Thabariy (224-310 H). This book is the first monumental work in early development of the Qur’anic interpretation and has been a main reference for commentators up to the present time. In fact, it is regarded as an unmatched encyclopedia in its field. How this book explores the chapter al-Fatihah makes the subject matter discussed in this article. The article analyzes the methods of interpretation used by al-Thabary in interpreting the chapter al-Fatihah through an exegesis approach, and comes up, through a critical content analysis, with results indicating that the structure of interpretation applied by al-Thabary in interpreting the chapter al-Fatihah is narrative (bi al-ma'tsur), while the method used is analytical (tahlily), and the style of analysis is socio-civic (adab-ijtima'iyi). Al-Thabary’s interpretation looks different from other commentators’ tradition not only for its being moderate in interpreting every phrase from the chapter al-Fatihah, but also for its relatively thorough exploration of different reading methods (qira'ah) have ever been applied for the chapter al-Fatihah.